Grammar Is Differentially Impaired in Subgroups of Autism Spectrum Disorders: Evidence from an Investigation of Tense Marking and Morphosyntax - Modyanova, Nadezhda; Perovic, Alexandra; Wexler, Ken (Frontiers in Psychology, 2017)
Deficits in the production of verbal inflection (tense marking, or finiteness) are part of the Optional Infinitive (OI) stage of typical grammatical development. They are also a hallmark of language impairment: they have been used as biomarkers in guiding genetic studies of Specific Language Impairment (SLI), and have also been observed in autism spectrum disorders (ASD). To determine the detailed nature of finiteness abilities in subgroups of ASD (autism with impaired language (ALI) vs. autism with normal language (ALN)), we compared tense marking abilities in 46 children with ALI and 37 children with ALN with that of two groups of nonverbal mental age (MA) and verbal MA-matched typically developing (TD) controls, the first such study described in the literature. Our participants’ performance on two elicited production tasks, probing third-person-singular -s and past tense -ed, from the Rice/Wexler Test of Early Grammatical Impairment (TEGI, Rice and Wexler, 2001), revealed extensive deficits in the ALI group: their ability to correctly mark tense was significantly worse than their much younger TD controls, and significantly worse than that of the ALN group. In contrast, the ALN group performed similarly to their TD controls. We found good knowledge of the meaning of tense and of case and agreement in both ASD groups. Similarly, both ASD groups showed distributions of null or overt subjects with nonfinite and finite verbs in line with those found in young TD children. A key difference, however, was that the ALI group used (rather than simply omitted) the wrong tense in some sentences, a feature not reported in the OI stage for TD or SLI children. Our results confirm a clear distinction in the morphosyntactic abilities of the two subgroups of children with ASD: the language system responsible for finiteness in the ALN group seems to be functioning comparably to that of the TD children, whereas the ALI group, despite showing knowledge of case and agreement, seems to experience an extensive grammatical deficit with respect to finiteness which does not seem to improve with age. Crucially, our ALI group seems to have worse grammatical abilities even than those reported for SLI.